Airborne observations of mercury emissions from the Chicago/Gary urban/industrial area during the 2013 NOMADSS campaign. (November 2016) - Gratz, L.E.; Ambrose, J.L.; Jaffe, D.A.; Knote, C.; Jaeglé, L.; Selin, N.E.; Campos, T.; Flocke, F.M.; Reeves, M.; Stechman, D.; Stell, M.; Weinheimer, A.J.; et al.
Abstract: Atmospheric emissions from the Chicago/Gary urban/industrial area significantly enhance ambient mercury (Hg) concentrations and lead to increased levels of atmospheric Hg deposition within the Lake Michigan Basin. We use airborne observations collected over Lake Michigan during the 2013 Nitrogen, Oxidants, Mercury, and Aerosol Distributions, Sources, and Sinks (NOMADSS) campaign to quantify the outflow of total Hg (THg) emissions from the Chicago/Gary urban/industrial area. We use concurrent airborne measurements of THg, carbon monoxide (CO), nitrogen oxides (NOx = NO + NO2 ), and sulfur dioxide (SO2 ) to calculate measured enhancement ratios and to characterize Chicago/Gary emissions with respect to the 2011 U.S. EPA National Emissions Inventory. We determine the observed THg/CO enhancement ratio in outflow from Chicago/Gary to be 0.21 ± 0.09 × 10 −6 mol mol −1 (ppqv/ppbv), which is comparable to observations reported for other major U.S. urban/industrial areas. We also employ the FLEXPART Lagrangian transport and dispersion model to simulate air mass transport during plume encounters and to compare our observations to inventoried emission ratios. We find that our observed THg/CO enhancement ratios are 63–67% greater than the transport-corrected emission ratios for the Chicago/Gary area. Our results suggest that there are many small emission sources that are not fully accounted for within the inventory, and/or that the re-emission of legacy Hg is a significant source of THg to the atmosphere in this region. Highlights: We made airborne observations of mercury and several co-pollutants near Chicago, IL. Using measurements in the urban outflow we quantify pollutant enhancement ratios. FLEXPART modeling is used to simulate transport of Chicago/Gary emissions. Observed mercury enhancement ratios are higher than inventoried emission ratios. Underestimates in the inventory and legacy emissions influence the observed offset.